Analogy in loss recovery mechanism upon the termination of the contract - Mikryukov, Viktor (Opción, 2019)
Based on a comparative analysis of Articles 524 and 393.1 of the Civil Code of the Russian Federation, the purpose of the study is to identify and propose a solution for the current problems of practical use and regulatory improvement of the mechanism for recovering abstract and specific losses. In result, improper use of the analogy mechanism in generalizing the rules of Art. 524 of the Civil Code of the Russian Federation by the Russian legislator has been identified. In conclusion, it is advisable to discard the indirect requirement of similarity or homogeneity of the substitute with the terminated contract.